ENHANCING READING SKILLS THROUGH POP-UP BOOKS IN NARRATIVE TEXT LEARNING - Permanasari, Pradnya; Putri Nindya Ayu Pamsuari (University of Kuningan, 2025)
This research aims to find out the problems that are faced by the students in reading skill and explain the pop-up book as a teaching medium can improve student’s reading skill in narrative text. The writer used classroom action research through two cycles design in this research. The respondent was XI-2 grade students of SMA N 1 Wiradesa that consisting of 31 students. The writer chose the XI-2 grade students because in this grade students should master of reading skill. In this research, the writer used qualitative design to gather the data. The data was collected through observation, open questionnaire, pre-test, and post-test. Based on data result of student's reading comprehension, it showed the significant improvement for reading comprehension using Pop-up book. The mean score of pre-test increased about 22.6% became 81.9 in post-test. Individually, students who had passed the KKM got a score of 75 or more were improved from only 14 or about 45.2% students in pre-test activity, then it had increased 100% became 31 students in post-test. Classically, all the students had passed the standard minimum score more than 75. It means the research ran successfully. Keywords: Pop-up Book; Reading Skill; Classroom Action Research